The effects of corporate and country sustainability characteristics on the cost of debt: An international investigation - Andreas Hoepner; Ioannis Oikonomou; Bert Scholtens; Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
We investigate the relationship between corporate and country sustainability on the cost of bank loans. We look into 470 loan agreements signed between 2005 and 2012 with borrowers based on 28 different countries across the world and operating in all major industries. Our principal findings reveal that country sustainability related to both social and environmental frameworks has a statistically and economically impactful effect on direct financing of economic activity. An increase of one unit in country sustainability scores is associated with an average decrease in the costs of debt by 64 basis points. Our analysis shows that the environmental dimension of a country's institutional framework is approximately two times as impactful as the societal dimension when it comes to determining the cost of corporate loans. On the other hand, we find no conclusive evidence that firm-level sustainability influences the interest rates charged to borrowing firms by banks.
urn:nbn:de:bsz:180-madoc-373942
Keywords: G14; G32; M14; 330; corporate social responsibility; CSR; CSP; sustainability; banking; financial contracts; culture